Observation of CP violation in B-+/- -> D K-+/- decays - Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2012)
An analysis of B ±→DK ± and B ±→Dπ ± decays is presented where the D meson is reconstructed in the two-body final states: K ±π ∓, K +K - and π +π -. Using 1.0 fb -1 of s=7TeV pp collisions, measurements of several observables are made including the first observation of the suppressed mode B±→[π±K∓]DK± CP violation in B ±→DK ± decays is observed with 5.8σ significance. © 2012 CERN.